Heat‐triggered thermo‐irreversible gelation of curdlan to control crystallisation and in vitro release of nobiletin. (3rd November 2022) - Li, Mengchen; Wang, Yueming; Guo, Dashan; Zhu, Kongdi; Zhang, Jiajia; Rong, Yujuan; Liang, Hongshan; Zhou, Bin
Summary: Many kinds of flavonoids with poor water solubility and high crystallisation properties tend to crystallise in the system, which negatively affects their processing, storage and bioavailability. Hence, controlling crystal growth is an effective pathway to achieve stabilisation. Inspired by the properties of heat‐triggered gelation of curdlan (Cur), the nobiletin (NOB) supersaturated solution was mixed with Cur gel under heating treatment, following which the formation of Cur gel might control NOB crystallisation process in situ . The results showed that different proportions of Cur could change the size of the crystals, of which a concentration higher than 4% could better control the crystallisation of NOB. The effect on texture and rheological properties after the addition of NOB was investigated in detail. Finally, in vitro release experiments showed that the gel played a great role in sustained release, greatly improving the release efficiency compared with pure NOB samples. Taken together, this study proposes a simple stabilisation method that initially attempts to overcome some of the bottlenecks in storage and processing of hydrophobic substances. Abstract : Schematic diagram of gel fabrication.